2006
DOI: 10.1099/mic.0.28816-0
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of potato aspartic proteases (StAPs) involves membrane permeabilization

Abstract: Solanum tuberosum aspartic proteases (StAPs) with antimicrobial activity are induced after abiotic and biotic stress. In this study the ability of StAPs to produce a direct antimicrobial effect was investigated. Viability assays demonstrated that StAPs are able to kill spores of Fusarium solani and Phytophthora infestans in a dose-dependent manner. Localization experiments with FITC-labelled StAPs proved that the proteins interact directly with the surface of spores and hyphae of F. solani and P. infestans. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 47 publications
5
42
0
5
Order By: Relevance
“…Here, we have shown that cysteine proteinases from latex induced the generation of H 2 O 2 in fungal spores of F. solani. These Wnding is similar to the results previously reported for an aspartic proteinase from Solanum tuberosum (Mendieta et al 2006).…”
Section: Identiwcation Of Pr-proteins In Latex Of C Procerasupporting
confidence: 91%
“…Here, we have shown that cysteine proteinases from latex induced the generation of H 2 O 2 in fungal spores of F. solani. These Wnding is similar to the results previously reported for an aspartic proteinase from Solanum tuberosum (Mendieta et al 2006).…”
Section: Identiwcation Of Pr-proteins In Latex Of C Procerasupporting
confidence: 91%
“…In plants, the production of proteases is believed to be a general defense mechanism against pathogenic fungi. Secretion of aspartic proteases with antimicrobial activity against Phytophthora infestans and the conidia of Fusarium solani has been described in potato tubers (Solanum tuberosum) after infection and damage to the intercellular fluids (Guevara et al, 2001(Guevara et al, , 2002(Guevara et al, , 2005Mendieta et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…In this regard, studies with APs from Solanum tuberosum have revealed their antimicrobial activity (Guevara et al 2002) including antifungal activity (Mendieta et al 2006). The authors cloned, expressed, and purified PSI (swaposin domain) from StAPs (StAsp-PSI) and found that the recombinant protein still maintained its cytotoxic activity (Muñoz et al 2010).…”
Section: Biotechnologically Engineered Aspartic Proteases and Industrmentioning
confidence: 96%
“…Most plant APs do not have particular roles, but some have been traditionally ascribed to roles such as hydrolysis of store proteins, stress response, plant senescence and programmed cell death, plant sexual reproduction (Simoes and Faro 2004), and antimicrobial functions (Mendieta et al 2006). Plant APs are widely distributed among gymnosperms.…”
Section: Native Plant Aspartic Proteasesmentioning
confidence: 99%